Peran Center Islamic of Administration Study (CIAS) Dalam Progam Sistem Jaminan Produk Halal Untuk Usaha Mikro Kecil Menengah - Salsabila Adawiyah Putri Andini; Syafanissa Aulia Fadia (Gunung Djati Conference Series, 2023)
It was written that the CIAS Institute is an institution that stands under the Department of Public Administration which focuses on the development of Islamic administration in terms of the development of social institutions. Based on the regulations of Law Number 33 of 2014 concerning Guarantees for Halal Products, which has been amended by Law Number 11 of 2020 concerning Job Creation, Decree of the Head of BPJPH No. 57 of 2021, the guidelines in the Al-Quran Surah Al-Baqoroh verse 168 are of course to make CIAS the basis for outreach to MSMEs.. this is because the CIAS institution has a connection with PKH UIN which has received legality directly from BPJPH. In solving it by dividing it from Edward's opinion which said that there were 4 factors that influenced the implementation of policies including: Communication, Resources, Position, Bureaucratic structure. The researcher chose the type of research using qualitative methods and with descriptive research strategies and interviews. The results of this study serve as a reference for CIAS' role as PPH, with the obstacles encountered, of course, becoming the role of CIAS in carrying out strategies to establish long-term cooperation and convince MSMEs who still do not know about policies and procedures for obtaining halal certification